Sastra Indonesia di Italia - S. Faizah Soenoto Rivai (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
Even though the Indonesian Language and Cultural Studies opened officially only in 1964, the tradition of studying Indonesia in general has long been an exotic 'hobby' for many Italians. Since a long time ago everything related with the 'Malay world' has been considered attractive. We are not only talking about the 20th century, but long before that. We should go back to the time the Italian explorers had their journeys in the Indonesian archipelago. The history of Italian exploration proves that the archipelago is not new to Italy. In their explorations, they showed their interests in local cultures, including language and traditional works of literature such as pantun. The vocabulary ist of A. Pigafetta (1512) is considered as the first dictionary' of Malay language in the western world. While E. Modigliani, in his time, already discussed about the Malay traditional poetry, pantun. In contrast to that, unfortunately, nowadays only a few contemporary works of Indonesian literature have bcen translated to Italian, three novels and some poems. The main reason for this is the fact that finding a publisher who is willing to publish such translations is not easy.